Doll dresses and fish - Unidentified artist (Colorado State University. Libraries, 1970)
This well sewn mola has tiny embroidery and appliqué stitches. Note that each horizontal stripe is a separate piece of hemmed fabric. Such striping was popular in the 1970s. The "doll dress" design was probably inspired by an advertisement.
This item was part of an exhibition at the Avenir Museum of Design and Merchandising titled Kuna Molas: Sewn Stories and the Interplay of Tradition and Change, August 18, 2014-July 31, 2015.
Cotton; 3 layers (maroon, black, turquoise); reverse and direct appliqué, embroidery.
Keywords: Molas -- Panama; Appliqué -- Panama; Embroidery -- Panama